Penerapan Sistem Informasi Manajemen Dipt.Jasa Raharja Cabang Sulawesi Selatan Kota Makassar - Lestari, Sintia Ayu; Ansari, Isa; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to determine the application of management information systems at PT. Jasa Raharja South Sulawesi Branch Makassar City. This study used qualitative research with data sources consisting of primary data and secondary data. The informants consisted of the Head of Service, employees and the community. Data collection techniques used observation and interview guidelines. Data analysis techniques were data reduction, data presentation and verification. The results of the study that the data input in the application of SIM based on online application had been applied by the PT. Jasa Raharja from the management, operational and technical aspects of insurance services. Data processing in SIM based on online application had been implemented well to provide convenience to customers and the public through the use of the JRku application, so that community data that had entered could be immediately processed by the PT. Jasa Raharja. Data output in the application of SIM based on online application had been implemented to increase the improvement of work results in providing services.